Application of the Rate-All-That-Apply (RATA) method to differentiate the visual appearance of milk powders using trained sensory panels. (October 2019) - Traill, Rachel M.; Luckman, Maree S.; Fisk, Nicolene A.; Peng, M.
Abstract: The appearance of food products has a critical impact on consumer perception and acceptability; however, there is little information available that robustly measures the appearance of food from a human perspective with the potential to quantitatively inform product developers on how their products are visually perceived and directions for modification. This study demonstrates a successful case of trained sensory panels differentiating the visual appearance presented in 145 non-reconstituted milk powder samples, representing 11 different types of milk powders, using the Rate-All-That-Apply (RATA) sensory method. The results obtained from nonparametric statistical analyses implied significant differences in certain attributes, yielding a clear discrimination between the different milk powders. Furthermore, an additional study, consisting of four repeated assessments of 10 selected samples, suggested high test-retest reliability within and between the testing days. Overall, results from this study indicate the potential of RATA for characterisation of visual appearance of food products using trained panellists.